PENANGANAN BIBIR SUMBING DAN MALFORMASI LANGITâ€LANGIT - Vimal Jairaman (Intisari Sains Medis, 2015)
Cleft lip or more recognized as labioschisis and palate malformation is a congenital defect that has the highest prevalence among infants. In this modern era of this problem can be seen as detected during the gestational age, but workarounds can only be done after the baby is born. Factors that cause labioschisis is still controversial, but the main factor that lead to labioschisis is genetic. The best cure for this problem is surgery. The management does not just stop after the surgery is done but sustained till that the children in school .